Can the ABCD Score be dichotomised to identify high-risk patients with transient ischaemic attack in the emergency department?. Issue 2 (24th January 2007) - Bray, Janet E; Coughlan, Kelly; Bladin, Christopher
Abstract : Background: Recent evidence shows a substantial short-term risk of ischaemic stroke after transient ischaemic attack (TIA). Identification of patients with TIA with a high short-term risk of stroke is now possible through the use of the "ABCD Score", which considers age, blood pressure, clinical features and duration of symptoms predictive of stroke. Aim: To evaluate the ability of dichotomising the ABCD Score to predict stroke at 7 and 90 days in a population with TIA presenting to an emergency department. Methods: A retrospective audit was conducted on all probable or definite TIAs presenting to the emergency department of a metropolitan hospital from July to December 2004. The ABCD Score was applied to 98 consecutive patients with TIA who were reviewed for subsequent strokes within 90 days. Patients obtaining an ABCD Score ⩾5 were considered to be at high risk for stroke. Results: Dichotomising the ABCD Score categorised 48 (49%) patients with TIA at high risk for stroke (ABCD Score ⩾5). This high-risk group contained all four strokes that occurred within 7 days (sensitivity 100% (95% confidence interval (CI) 40% to 100%), specificity 53% (95% CI 43% to 63%), positive predictive value 8% (95% CI 3% to 21%) and negative predictive value 100% (95% CI 91% to 100%)), and six of seven occurring within 90 days (sensitivity 86% (95% CI 42% to 99%), specificity 54% (95% CI 43% to 64%), positive predictive value 12.5% (95% CI 5% to 26%) and negative predictive value 98% (95% CI 88% to 100%)). Removal of the "age" item from the ABCD Score halved the number of false-positive cases without changing its predictive value for stroke. Conclusion: In this retrospective analysis, dichotomising the ABCD Score was overinclusive but highly predictive in identifying patients with TIA at a high short-term risk of stroke. Use of the ABCD Score in the emergency care of patients with TIA is simple, efficient and provides a unique opportunity to prevent stroke in this population of patients.